Synthesis of Substituted 1-Benzyl-2H-1,2,3-Triazoles by a Click Reaction Using Calcium Carbide as an Acetylene Source - Fu, Rugang; Lei, Yuming; Wang, Yuyu; Huang, Baoqian; Qiu, Dong; Wang, Junke (Synlett, 2024)
An effective strategy for constructing substituted 1-benzyl-1H-1,2,3-triazoles was developed through click reactions of benzylic halides with sodium azide and calcium carbide as sources of nitrogen and acetylene, respectively. The advantages of this method are an easily handled inexpensive source of acetylene, a wide range of substrates, satisfactory yields, and simple workup procedures, which could promote the use of calcium carbide as a sustainable acetylene source in modern industrial chemistry.
Keywords: sodium azide; calcium carbide; click chemistry; benzyl halides; triazoles